Gamma‐aminobutyric acid (GABA) levels in the midcingulate cortex and clozapine response in patients with treatment‐resistant schizophrenia: A proton magnetic resonance spectroscopy (1H‐MRS) study. Issue 11 (16th September 2022) - Ueno, Fumihiko; Nakajima, Shinichiro; Iwata, Yusuke; Honda, Shiori; Torres‐Carmona, Edgardo; Mar, Wanna; Tsugawa, Sakiko; Truong, Peter; Plitman, Eric; Noda, Yoshihiro; Mimura, Masaru; Sailasuta, Napapon; et al.
Abstract : Background: Gamma‐Aminobutyric Acid (GABA) is the primary inhibitory neurotransmitter in the central nervous system. GABAergic dysfunction has been implicated in the pathophysiology of schizophrenia. Clozapine, the only approved drug for treatment‐resistant schizophrenia (TRS), involves the GABAergic system as one of its targets. However, no studies have investigated the relationship between brain GABA levels, as measured by proton magnetic resonance spectroscopy ( 1 H‐MRS), and clozapine response in patients with TRS. Methods: This study enrolled patients with TRS who did not respond to clozapine (ultra‐resistant schizophrenia: URS) and who responded to clozapine (non‐URS), patients with schizophrenia who responded to first‐line antipsychotics (first‐line responders: FLR), and healthy controls (HCs). We measured GABA levels in the midcingulate cortex (MCC) using 3T 1 H‐MRS and compared these levels among the groups. The associations between GABA levels and symptom severity were also explored within the patient groups. Results: A total of 98 participants (URS: n  = 22; non‐URS: n  = 25; FLR: n  = 16; HCs: n  = 35) completed the study. We found overall group differences in MCC GABA levels ( F (3, 86) = 3.25, P  = 0.04). Specifically, patients with URS showed higher GABA levels compared to those with non‐URS ( F (1, 52) = 8.40, P  = 0.03, Cohen's d  = 0.84). MCC GABA levels showed no associations with any of the symptom severity scores within each group or the entire patient group. Conclusion: Our study is the first to report elevated GABA levels in the MCC in patients with schizophrenia resistant to clozapine treatment compared with those responsive to clozapine. Longitudinal studies are required to evaluate if GABA levels are a suitable biomarker to predict clozapine resistance.